1989
DOI: 10.1192/bjp.155.6.735
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Manifestations of Frontal Lobe Tumours

Abstract: In a recent article in the British Medical Journal Maurice-Williams & Dunwoody (1988) reported two patients with frontal meningiomas who presented initially to psychiatrists. The correct diagnosis was made in one of them after prolonged, perhaps unnecessary, psychiatric treatment. In the other the diagnosis was made at autopsy. In this case psychiatrists were only briefly involved and neurosurgical referral had been made promptly. The authors, who treat these reports as a cautionary tale, conclude by warni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Nevertheless, studies have reported no raised incidence of intracranial tumors among patients manifesting schizophrenia, affective illness, or neurotic symptoms [27]. A very small incidence of positive radiological findings in psychiatric patients, except for brain atrophy, does not give good reason for routine CT and MRI brain scans in all hospitalized psychiatric patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies have reported no raised incidence of intracranial tumors among patients manifesting schizophrenia, affective illness, or neurotic symptoms [27]. A very small incidence of positive radiological findings in psychiatric patients, except for brain atrophy, does not give good reason for routine CT and MRI brain scans in all hospitalized psychiatric patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…Mental changes, including dementia, are commonly seen in patients with cerebral tumours (Lishman, 1987; Ron, 1989). Their occurrence is influenced by: the site, being commonest in frontal lobe; the type of tumour, the more invasive (usually malignant) the more commonly they are seen (Hacaen and Ajuriaguerra, 1956); the presence of raised intracranial pressure; and the rate of growth of the tumour (Lishman, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The classical descriptions of mental abnormalities in brain tumours (Ron, 1989) fall into three broad categories; confusional states, mood or behaviour disturbances mainly of organic type and paroxysmal disturbance. The above two cases do not fit these categories but comprise the rarer group of those who seem to have well defined "functional" disorders.…”
Section: Discussionmentioning
confidence: 99%
“…So far most of the attention has concerned the anterior fossa, particularly the frontal lobe (Ron, 1989;Maurice Williams and Dunwoody, 1988). There are goods reasons for this.…”
Section: Introductionmentioning
confidence: 99%